Is Investment Contributing to Competitiveness in Nautical Tourism in the Atlantic Area? - Santos, Eleonora (2022)
The blue economy contributes significantly to the creation of the Atlantic Area’s identity. In addition, the search for outdoor experiences after the COVID-19 lockdown suspensions has renewed the popularity of nautical tourism in this area and in the world. Despite the negative effects of the economic crisis on tourism, evidence suggests that some tourist destinations in the Atlantic area are resilient. Thus, whereas some branches of the blue economy face considerable challenges to increasing competitiveness, others offer opportunities for economic growth and employment. In this context, investment is necessary to lay the foundations for the sustainable development of nautical tourism. However, regarding the role of investment in productivity and competitiveness in the context of crisis, there is no consensus among academics. Thus, we investigate whether the investment contributed to competitiveness in nautical tourism in the Atlantic Area in 2016–2020. We collected data from ORBIS for 29 nautical-tourism companies and performed a quantitative and qualitative narrative analysis of competitiveness indicators, enabling comparisons pre and during crisis. The results highlight the multiplicity of ways in which crisis impacts nautical-tourism firms. The research fills a gap in the literature by investigating the dynamic capabilities of nautical-tourism SMEs in periods of recession, with a special focus on restructuring and competitiveness strategies. Some recommendations are outlined to promote the efficiency of resources and stimulate the competitiveness of companies to allow the regional development of nautical tourism in the territory of the Atlantic area.